Academician of the NAS of Ukraine Vadym Mykhailovych Loktev (to the 75th anniversary of his birthday) - Zagorodny, A. G.; Izotov, Yu. I.; Petrov, E. G.; Lev, B. I.; Gusynin, V. P.; Sitenko, Yu. A.; Brizhik, L. S. (Ukrainian Journal of Physics, 2020)
-